Wəlastəkwey (Maliseet) Homeland: Waterscapes and Continuity within the Lower St. John River Valley, 1784-1900 - Pawling, Micah (Acadiensis, 2017)
After decades of intense immigration to the lower St. John River Valley, the Maliseets, the Indigenous people of this watershed, struggled to inhabit the southern portion of their homeland. The Maliseets, though, successfully retained their cultural attachment to the lower river, the lakes, and the coast through birchbark technology and fishing. Their historical memory also provided alternative narratives to dispossession and conveyed a waterscape where Indigenous lifestyles coexisted with societies in New Brunswick. And while some Maliseet families chose to live beyond their reserve villages, Indigenous leaders secured two small reserves at The Brothers (Kennebecasis Bay) and Oromocto.